A Review of the Literature on Gender and International Family Joint Migration - Freitas-Monteiro, Teresa (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2024)
Most migration decisions are not made by isolated individuals but by families or entire households. However, international family migration remains an understudied field. This article provides an overview of the literature on gender and family dynamics as a path to understanding the family decision to migrate internationally. The first three sections summarize the major historical trends and economic theories on the gender pay gap and give a brief overview of the neoclassical migration model and household models in economics. The central section of this article documents the models of family migration in economics and sociology. Despite the recent improvements, the analysis of family migration still lags far behind that of individual migration and can gain from incorporating gender-theories and the recent developments in household models.